Can shifting attention to accuracy reduce misinformation on social media? A replication and extension in China - Zhiming Liu (Humanities & Social Sciences Communications)
Abstract The inattention-based theory of Pennycook et al. (2020) holds that because social media context focuses attention on factors other than accuracy the sharing of online misinformation is often unintentional. They provided evidence in the context of COVID-19 misinformation by conducting two survey experiments with more than 1700 U.S. participants. The present study replicates and expands on the original study of Pennycook et al. (2020) through research on the spread of misinformation about COVID-19 in China. The study recruited 1319 participants through the Credamo platform for three survey experiments and found support for the original findings. First, participants discern far less between true and false information when asked about share intention compare to when asked about the accuracy of the information. Second, an intervention that nudges people to think about accuracy by asking participants to evaluate the accuracy of information unrelated to COVID-19 can significantly improve the quality of information sharing. Third, inattention-based theory can explain more than 37% of COVID-19 misinformation sharing in China.